Police Reform in Thailand Post-2006 - Poothakool, Krisanathong; Glendinning, Tony (International Journal of Criminology and Sociology, 2013)
<!– [if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> <!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –> The study analyses the operation and culture of Thai policing and the intersection between policing and politics framed by the recommendations of the Police Reform Committee (PRC), 2006—2007. The PRC’s priorities were: devolving police administration, especially budgets and personnel management; increasing accountability, especially establishing an Independent Complaints’ Committee; and civilianization. Those priorities were seen as clearing the ground for development of community-oriented policing longer-term. Interviews were conducted with senior members of the PRC. Afterwards non-commissioned officers’ opinions were established through a countrywide survey and follow-up in-depth interviews. Their station chiefs were also interviewed. According to PRC members and serving officers’ accounts the barriers to reform of police administration were political interference and nepotism, especially corruption of appointments, nominations, promotions and transfers. Local policing often involved further interference by informal networks of officials, politicians and business. The PRC’s recommendations were shelved due to an unfavourable political climate. The paradox was the PRC’s strategies for ‘democratic’ police reform were well-informed and well-founded but its establishment had been politically motivated and it was not immune to interference by competing political factions. The study contributes to debates about moving away from authoritarian policing models in the developing world by analysing barriers to the reform of police administration in the Thai context.